Misconceptions about health and disease prevention behaviors of rural Appalachian Americans - Miller, Wayne; Griffith, Brian; Bikman, Timothy; Meyer, Cameron (International Journal of Medicine, 2014)
Background: Appalachia is one of the unhealthiest regions in the United States due to poor disease prevention behaviors. Objective: Determine if self-perceived health of rural Appalachians is related to participation in disease prevention behaviors. Methods: Rural Appalachian adults (n=437) were surveyed regarding their self-perceived health and disease prevention behaviors. Healthy behaviors included: moderate (? 90 min/wk) and vigorous (? 45 min/wk) physical activity, sugared drink consumption (? 1 sugared drink/d), smoking (non-smoker), alcohol consumption (? 1 drink/d), blood pressure (? 120/80 mm Hg), and fast food consumption (? 1 time/wk). Participants were grouped where healthy = (self-health rating > 5 on a 0-10 scale), BMI < 25, and blood pressure (? 120/80 mm Hg). Jaccard Binary Similarity (JBS) coefficients and Russell and Rao (RR) dichotomy coefficients determined the association and predictability of self-health ratings and disease prevention behaviors. T-tests determined group differences in the number of disease prevention behaviors. Results: Individuals who reported being healthy had high JBS coefficients for having healthy sugared drink consumption (0.552), not smoking (0.704), low alcohol consumption (0.742), and low fast food consumption (0.481). RR results were similar to JBS results. Not smoking and low alcohol consumption were highly correlated (r=0.87). Those with a good health perception practiced more disease prevention behaviors (mean±SEM, 2.84±0.06) than those with a poor health perception (2.19±0.10, p<0.001). Good health perceptions were not strongly related to obesity and inactivity. Conclusions: Appalachians are not indifferent about their health. However, Appalachians may not understand how inactivity and obesity relate to disease. Keywords: Disease Prevention, Health Behaviors, Rural Appalachian Health, Self-Perceived Health.